Journey to crime of 'itinerant crime groups' - Van Daele, Stijn (Policing, 2010)
Purpose - Most researchers have found that property crimes have a local focus: offenders tend to operate in the vicinity of their residence. This has led the police to organise themselves to concentrate their resources in highly populated, urban areas, Over the last decade mobile property offenders have been found in various Western European countries that differ from this norm. These groups of mainly Eastern European multiple offenders engaging in property crime tend to travel further than other offenders. As such, their operations differ from most criminals, challenging the way the police are organised and undermining criminological theories on journey to crime. The aim of this paper is to look at the specificity of mobility patterns of these groups, to examine the precise interpretation of their mobility and to consider the implications. Design/methodology/approach - The paper uses the Belgian police database containing all serious property crimes in Belgium for the period 2002-2006. Some basic offender characteristics have been identified and for these offenders journey-to-crime patterns have been established. Findings - Eastern European multiple offending groups tend to commit their crimes in rural areas. Although they start their journey in regions considered "crime importing", they carry out their crimes in "crime exporting" areas. As such, they are atypical, challenging traditional theories on journey-to-crime and the way in which police forces are organised. Research limitations/implications - Observing a special group is one thing, but explaining these differences is another. Further research is needed, in particular with regard to the motivational aspects for these offenders. Originality/value - Whereas most researchers have found crime (including property crime) to be mainly local, the present research focuses on more mobile offenders. The challenges that these groups create for law enforcement authorities make it important for them and their patterns of activity to be understood